Evaluating a CD-ROM product : a case study of the Singapore trade connection - Noor Faridah A. Rahim. (2009)
Information retrieval from CD-ROM databases has added a new dimension enabling users to retrieve voluminous amounts of information conveniently. The Trade Development Board (TDB) has capitalised on this technology by developing the Singapore Trade Connection CD-ROM (STC) which provides comprehensive business and trade-related information to businessmen in the comfort of their offices.